Attenuation of oxidant/antioxidant imbalance during treatment of exacerbations of chronic obstructive pulmonary disease. Issue 6 (June 1997) - Rahman, I; Skwarska, E; MacNee, W
Abstract : BACKGROUND: An oxidant/antioxidant imbalance is thought to occur in patients with chronic obstructive pulmonary disease (COPD). It has recently been shown that during exacerbations of COPD the antioxidant capacity and protein sulfhydryls of plasma are lower and the levels of products of lipid peroxidation are higher than in age matched healthy subjects. The aims of this study were to confirm these data and to measure the time course of these changes. METHODS: The plasma Trolox equivalent antioxidant capacity (TEAC), protein sulfhydryls, and products of lipid peroxidation were measured throughout the course of treatment in 13 patients who presented with an acute exacerbation of COPD. RESULTS: TEAC values (mmol/l) were low on admission (mean 0.67, 95% confidence interval (CI) 0.32 to 0.88; p < 0.05) and had increased by discharge (0.98, 95% CI 0.88 to 1.2; p < 0.05) but still remained lower than in healthy subjects (1.33, 95% CI 1.11 to 1.65). There was also restoration of plasma protein sulfhydryl levels (mmol/l) from admission (0.32, 95% CI 0.20 to 0.43) to discharge (0.49, 95% CI 0.42 to 0.62, p < 0.001) to levels similar to those in healthy subjects (0.52, 95% CI 0.43 to 0.65). Products of lipid peroxidation, measured as thiobarbituric acid-malondialdehyde adducts (mumol/l), were significantly higher (2.08, 95% CI 1.8 to 2.5) than in control subjects (1.3, 95% CI 0.85 to 1.32; p < 0.01) and returned to normal values by the time of discharge (1.2, 95% CI 0.88 to 1.29). CONCLUSIONS: These data confirm the presence of a profound oxidant/antioxidant imbalance in the blood of patients with acute exacerbations of COPD which returns towards normal values during the course of treatment.